2017
DOI: 10.1111/nmo.13258
|View full text |Cite
|
Sign up to set email alerts
|

Diminished gastric prokinetic response to ghrelin in a rat model of spinal cord injury

Abstract: Hypophagia accompanying T3-SCI produces a significant and physiologically appropriate elevation in serum ghrelin levels. However, higher ghrelin levels did not translate into increased gastric motility in the acute stage of T3-SCI. We propose that this may reflect diminished sensitivity of peripheral vagal afferents to ghrelin or a reduction in the responsiveness of medullary gastric vagal neurocircuitry following T3-SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These data suggest that T3-SCI provokes unparalleled structural and functional changes with variable duration. Our accumulating evidence suggests that SCI provokes impairments in the vagal afferent signaling necessary for proper GI reflexes (Besecker et al, 2018;Holmes, 2012;Tong et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that T3-SCI provokes unparalleled structural and functional changes with variable duration. Our accumulating evidence suggests that SCI provokes impairments in the vagal afferent signaling necessary for proper GI reflexes (Besecker et al, 2018;Holmes, 2012;Tong et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent reduction of GI chemosensory signaling to medullary neural circuits (Besecker et al, 2018;Tong et al, 2011) raises the question of pathophysiological remodeling of vagal afferent fibers following SCI. Using molecular techniques and in vivo electrophysiological recordings of the vagal afferent fibers innervating the stomach, we tested the hypothesis that acute and chronic high-thoracic (spinal level T3) SCI attenuate gastric mechanosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, GHSR signaling does not specifically recruit any of the referred signaling proteins and, consequently, the referred functional studies may involve indirect actions of ghrelin on the DMNV. Electrophysiological recordings in rat brain slices indicated that ghrelin increases the frequency but does not affect the amplitude of spontaneous glutamatergic currents of DMNV neurons, an indication that such effect is mainly indirect ( Besecker et al, 2018 , Swartz et al, 2014 ). GHSR mRNA is present in the Amb of rats and mice, as revealed by ISH ( Bron et al, 2013 , Scott et al, 2012 , Zigman et al, 2006 ), and fluorescent cells were observed in the Amb of the GHSR-eGFP mice ( Mani et al, 2014 ).…”
Section: Evidences Unmasking Direct Targets Of Ghrelin At the Vagus N...mentioning
confidence: 96%
“…Neuroendocrine activity is regulated by neural and humoral factors, including autonomic nerve activity (Besecker et al, 2018 ; Breit et al, 2018 ; Bonaz, 2022 ). For example, both intrapancreatic ganglia and extrapancreatic nerves have an important influence on pancreatic endocrine function (Li et al, 2019 ).…”
Section: Neural Regulation Of Neuroendocrine Activitymentioning
confidence: 99%